Northwest Passage Shipping in the 21st Century - Campbell, Alex; Sajbel, Josie; Tuttle, Collin (My University, 2018)
In recent decades, the Arctic has been warming at double the rate of the global average. This has led to a significant loss of ice cover, including 33% of sea ice extent and 63% of total ice volume in September. There is renewed interest in trans-Arctic shipping as the diminishing ice cover significantly reduces costs and journey times between Asia, Europe, and North America. We will examine the suitability of various routes through the Northwest Passage and determine the optimal route based on ice conditions, bathymetry, ship attributes, and various other factors throughout the 21st century.
Includes Tables, Charts, Graphs, Equations, Maps, Appendices and Bibliography.
Keywords: Northwest Passage; Shipping